An E-Prime Study on the Cognitive Mechanisms of English Predicative Metaphor Comprehension by Chinese EFL Learners - Su, Yuanlian; Liu, Jie (English language teaching (Toronto), 2020)
Studies on predicative metaphors like "The rumor flew through the office" have not received due attention until recently. Through a behavioural experiment, this study investigates the cognitive mechanisms as well as the effects of familiarity on Chinese EFL learners' comprehension of English predicative metaphors, adopting a two factors within-subject design: 2 (degree of familiarity: high-familiarity, low-familiarity) x 3 (priming condition: matching priming condition (MP), mismatching priming condition (MMP) and, no priming condition (NP)). Forty-five third-year Chinese undergraduate students participated in the experiment by completing a metaphor semantic comprehension test. Their reaction times (RTs) and accuracy rate of comprehension were recorded and a two-way ANOVA analysis of the results reveals that: Embodied simulation mechanism plays an important role in English predicative metaphor processing, especially when the metaphors being processed are unfamiliar. Yet its role diminishes when the metaphors being processed are highly familiar, which encourages the use of the language processing mechanism. To conclude, Chinese EFL learners make use of either the embodied simulation mechanism or the language processing mechanism in comprehending predicative metaphors, depending on their varying degrees of familiarity. These findings shed light on predicative metaphor instruction in L2 English teaching.